Myc requires RhoA/SRF to reprogram glutamine metabolism. (4th May 2018) - Haikala, Heidi M.; Marques, Elsa; Turunen, Mikko; Klefström, Juha
ABSTRACT: RhoA regulates actin cytoskeleton but recent evidence suggest a role for this conserved Rho GTPase also in other cellular processes, including transcriptional control of cell proliferation and survival. Interestingy, loss of RhoA is synthetic lethal with oncogenic Myc, a master transcription factor that turns on anabolic metabolism to promote cell growth in many cancers. We show evidence indicating that the synthetic lethal interaction between RhoA loss and Myc arises from deficiency in glutamine utilization, resulting from impaired co-regulation of glutaminase expression and anaplerosis by Myc and RhoA – serum response factor (SRF) pathway. The results suggest metabolic coordination between Myc and RhoA/SRF in sustaining cancer cell viability and indicate RhoA/SRF as a potential vulnerability in cancer cells for therapeutic targeting.